Knowledge-based eligibility assessment system / Ruziah Puasa - Puasa, Ruziah (1999)
Knowledge-based eligibility assessment system is systems that can be used in order to choose only the applicable applicant who want to buy a house. This system is build only for low cost housing. The system can also able to evaluate whether someone is applicable or not in a few times without asking the applicant the questions. So, in order to evaluate the applicant data, knowledge based system method has been used. It is because all the data and rules is stored in the database. If the data match all the rules, the applicant will be able to be the owner, else whether he or she in waiting list or cannot be the owner. So, by looking throughout the project, it can help the user to process data faster. Furthermore the system can produce reports such as applicant data, also when someone wants to know their result, system will give the answer in a few second.